Molecular Modelling Analysis of the Axial Distortion of the Coordination Geometry Around Copper(II) in Octahedral Ligand Fields - Huq, Fazlul (Asian Journal of Chemistry, 2010)
Molecular modelling analysis using molecular mechanics, semi-empirical DFT calculations were carried out to investigate JahnTeller effect in Cu2+ placed in octahedral ligand fields. The results show that both semi-empirical and DFT calculations can predict the axial distortion in octahedral Cu(lI) complexes. However, the agreement between observed and calculated Cu(II) ligand distances are found to be much greater with DFT calculations than with semiempirical calculations.